The good goodbye: helping children through transitions using storytelling - Claire McNicol (Scottish Journal of Residential Child Care)
Storytelling is an age-old tradition in Scotland and indeed throughout the world. Macintyre's (2003) work on Mull, for example, documents how storytelling grew and developed more strongly as the traditional communities declined. A growing interest in storytelling as a possible technique to help children deal with many life situations has been emerging in Scotland, and indeed in other countries, over the past few years.